Metabolic and Inflammatory Aspects of Iron Deficiency in Obese - Perko, Agnieszka; Niedźwiedzka, Monika; Rosińska, Kamila; Łojewska, Julia Natalia; Janicka, Ewelina Justyna; Bochenek, Oliwia; Koper, Mateusz; Rosiński, Mateusz (Quality in Sport, 2024)
Obesity is a chronic disease with a complex etiology, characterized by a persistent inflammatory state induced by various pro-inflammatory cytokines, including interleukin-6. This condition leads to increased production of hepcidin, a protein hormone responsible for regulating iron homeostasis. Hepcidin's primary function is to inhibit iron absorption by enterocytes, the cells lining the small intestine. Symptoms of iron deficiency, which is crucial for oxygen transport, energy production, and immune system support, can be varied and often nonspecific, such as general weakness, pallor, or concentration difficulties, potentially prolonging the diagnostic process. This article aims to analyze the relationship between obesity and iron deficiency in the metabolic context. Obesity, being one of the most prevalent health issues of the modern world, is associated with numerous complications, including disturbances in iron metabolism. Iron deficiency in obese individuals can lead to anemia, reduced physical performance, and cognitive impairments. Traditional treatment methods for this micronutrient deficiency involve supplementation. However, supplementation shows reduced efficacy in overweight and obese individuals, likely due to elevated hepcidin levels. A more effective approach should include interventions targeting not only the supplementation of the missing micronutrient but also weight reduction.